Applied quantum mechanics - Osborn, Richard K. (World Scientific, 1988)
This is book introduction about the simple shell model, introduction to reaction rates, neutron-nuclear cross-sections, some applications, a hamiltonian for nonrelativistic, spinless charged paticles in the presence of electromagnetic fields...